2012
DOI: 10.1002/14651858.cd009009.pub2
|View full text |Cite
|
Sign up to set email alerts
|

General health checks in adults for reducing morbidity and mortality from disease

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
200
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(218 citation statements)
references
References 202 publications
8
200
0
10
Order By: Relevance
“…However, our findings mirror those of a pragmatic, parallel-group, cluster-randomised trial in 33 general practices in eastern England (ADDITION-Cambridge) [8], in which screening for type 2 diabetes in those at high risk did not result in a reduction in all-cause or cardiovascular-or diabetesrelated mortality rates over 10 years. Our results also reaffirm a recent Cochrane review [10], which found no long-term impact of general health checks on mortality and morbidity rates following population screening.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our findings mirror those of a pragmatic, parallel-group, cluster-randomised trial in 33 general practices in eastern England (ADDITION-Cambridge) [8], in which screening for type 2 diabetes in those at high risk did not result in a reduction in all-cause or cardiovascular-or diabetesrelated mortality rates over 10 years. Our results also reaffirm a recent Cochrane review [10], which found no long-term impact of general health checks on mortality and morbidity rates following population screening.…”
Section: Discussionsupporting
confidence: 91%
“…There are relatively few trials assessing the benefits and harms of screening at the population level [8,9]. A Cochrane review of randomised trials comparing health checks with no health checks in adult populations found that they did not reduce morbidity, all-cause mortality or cardiovascular-related mortality rates, although the number of new diagnoses increased [10]. The review included data from a number of historical cohorts that were initiated before the widespread introduction of effective treatments such as statins.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of routine periodic health reviews does not seem to add value. Indeed, two very large systematic reviews and meta-analyses concluded that general practice periodic health increased medication utilization and use of diagnostic testing but did not accrue any net benefit in terms of improved overall or disease specific mortality (2,3). Similarly, in most cases, undirected, population-wide screening for most chronic conditions does not add value to targeted screening of patients presenting for episodic health care who are opportunistically identified as having clinical risk factors for a target condition.…”
mentioning
confidence: 99%
“…A recent example of a Cochrane review that has important clinical and policy implications concerns the use of general health checks in adults, shown not to reduce morbidity and mortality, despite the fact that the UK government began a policy of health checks for adults in 2009. 6 We urge readers to take a more critical view of the medical literature and its relevance to their clinical practice. Cochrane reviews remain key components for GPs who wish to remain safe and effective doctors.…”
mentioning
confidence: 99%